The Derivational And Inflectional Affixes Used by Commentators on Nessie Judge's YouTube Video - Shakti, Dyah Ayu Candra; Shofiya, Arina; Eftanti, Erna (Centre for Literary and Cultural Studies, 2024)
Indonesia is one country which provides English learning for students from elementary to senior high school levels. The use of English is not only applied in formal situations such as school but also in informal situations such as using social media. The most popular social media used is YouTube. There is a comment feature that helps users leave comments to interact with each other. One of the contents that have a lot of comments is Nessie Judge, which talks about horror and conspiracy theories. What's interesting about this channel is that even though the content is in Indonesian, many comments are found in English. From this, the researcher tries to find out what types of affixes are often used in informal use.1) What are the types of derivational affixes used by commentator Nessie Judge's video on YouTube? 2) What are the types of Inflectional affixes used by commentator Nessie Judge's video on YouTube? To answer this question, the researcher uses a descriptive study with a qualitative approach to the 12 comments in Nessie Judge Video. From this study it was found that all types of Derivational affixes can be found such as Nominalizer, Verbalizer, Adverbializer, and adjectivalizer. Another result found that the type of Inflectional affixes was also found, namely type plural suffixes, third-person –singular present tense suffixes, present participle suffixes, past tense suffixes/ past participle suffixes, possessive suffixes, comparative degree suffixes. Also, for types of inflectional affixes or superlative degree suffixes you can see in the YouTube comments in the video.